Análisis a la gestión económica- financiera de la empresa “Ferrocomercial Vera”, periodo 2019-2022 - Cañar Obaco, Nayeli Liliana (2023)
Small and medium-sized enterprises (SMEs) are distinguished by their minimum number of workers, production level, income, and others. They have a significant contribution to the generation of employment. Therefore, they contribute to the economy and production in Ecuador. Therefore, this work aims to analyze the economic-financial management through indicators that allow knowing the company's current state, "Ferrocomercial Vera". The research has adopted a quantitative and qualitative approach with a transversal and longitudinal design. The study is descriptive-explanatory and mathematical; the method used was deductive and analytical. According to the results obtained from the research, the financial analysis reflects that the company is based mainly on its sales according to the inventory item, being the most representative account of the current assets with 54%, i.e., the goods available for sale and these represent the primary source of income to settle debts or its obligations. Regarding the application of financial indicators to analyze profitability, positive results are detailed in terms of ROA with 3% to 5% in the periods 2019 to 2022, in the application of ROE of equity with 12% and on equity with 19%, obtaining good profitability, it should be emphasized that this indicator is the primary key to success to know the performance of the company and stay in the market. It can be concluded that it is essential to carry out a deep financial analysis of the company, with the help of financial tools, because they allow correct management of the financial statements, to analyze and evaluate its current situation, and to correct possible risks to make good future decisions.